Quality of Tests of Expectation Formation for Revised Data - Ziembińska, Paulina (Central European Journal of Economic Modelling and Econometrics, 2021)
The work contains discussions and simulation analyses of the expectation formation processes, taking account of the data revisions. In particular, it contains results of simulations examining statistical properties of the rationality tests and extrapolation processes, with particular focus on their behaviour in the case of short samples and data with measurement errors. The conclusions indicate that the rationality test based on the optimal regression and the proposed adaptive and accelerating tests are the most efficient and flexible. The tests showcasing best properties have been applied to a new set of macroeconomic forecasts for Poland. The results show that there are no grounds for rejecting the hypothesis on the rationality of forecasts derived from the National Bank of Poland (NBP) and the Organisation for Economic Cooperation and Development; however, this property was rejected for the European Commission. What is more, the comparative analysis indicates that only the national institution (NBP) may potentially aim the final readings of the macroeconomic data as the forecasting target. Finally, it transpires that the extrapolative models, albeit simple and intuitively interpreted, generally fail to correctly explain the forecast formation processes regarding the Polish economy.